Assemblages of Trichoptera larvae on water moss in the middle reaches of the Yenisei River (Siberia, Russia) - Konovalova, Daria A.; Kislitsina, Nadezhda I.; Zotina, Tatiana A. (Zootaxa, 2023)
This study provides first data on species composition of trichopterans inhabiting water moss, Fontinalis antipyretica Hedw., in the middle reaches of the Yenisei River. Analysis of Trichoptera larvae collected from samples of water moss in tail waters of the Krasnoyarsk Hydroelectric Plant in 2008–2021 revealed nine species of the order, which belonged to four families. Among them, six species belonging to the Limnephilidae family have not been mentioned in previous studies of the Yenisei invertebrates. Images of species are provided. One species, Apatania crymophyla McLachlan, was the most dense in all samples of water moss. The densities of A. crymophyla in samples of water moss in 2021 ranged within 1.2–7.0 thousand individuals / kg f.w. Other representatives of the order occurred in samples of water moss sporadically or consistently but in very low densities, which did not allow reliable quantification of their abundances. Consequently, numerous large clumps of water moss in the fast-flowing waters of the Yenisei favor an abundance of Trichoptera larvae, providing these insects refuge, food, and material for their cases. However, the reasons for the predominance of one species, A. crymophyla, are to be elucidated in further studies. The present study suggests that the contributions of Trichoptera and the total invertebrate community inhabiting water moss to biomass and energy budgets in the Yenisei have been usually underestimated before now. Hence, seasonal trends of species composition and abundance of invertebrates associated with water moss in the Yenisei River, including comparison with the entire zoobenthic community, are to be studied in the future.